DEFINITION OF INDICATORS OF RELIABILITY OF CARS - R. V. Guseynov; L. M. Sultanova (Вестник Дагестанского государственного технического университета: Технические науки)
Definition of reliability, durability, their principles, methods and regularities in relation to motor transport is given.